Aromatic imine triazole polymer film and its preparation method and application
By using arylimine triazole polymer materials, thin films with excellent high and low temperature resistance and high thermal conductivity are designed and prepared, which solves the problem of insufficient thermal conductivity of existing polymer films and is suitable for thermal management applications in high-tech fields.
Patent Information
- Application Number
- CN202411657503.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing polymer films have low thermal conductivity and heat dissipation performance, which limits their application in high-tech fields, especially in high-temperature and high-frequency electronic products, which are difficult to meet the thermal management needs.
Arylimine triazole polymer is used as a material to form a thin film with excellent high and low temperature resistance, good film formation and high thermal conductivity through specific structural design and preparation methods.
It has achieved high thermal conductivity and good mechanical properties of the aromatic imine triazole polymer film, can maintain stable thermal conductivity under extreme temperature conditions, and meet the thermal management needs of high-tech fields such as electronic products.
Smart Images

Figure CN119161734B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high molecular polymers, in particular to an aromatic imine triazole polymer film and a preparation method and application thereof. Background Art
[0002] As the operating frequency, integration, and power density of electronic products continue to increase, effective thermal management is becoming increasingly urgent. Designing effective thermal management systems to manage the accumulation of excess heat is crucial. The primary strategy for thermal management is to transfer excess energy from electronic products to the outside through thermally conductive materials. Compared to traditional thermal management materials, thermally conductive films with high in-plane thermal conductivity have attracted significant attention as emerging candidate materials over the past decade, demonstrating significant potential for thermal management applications in next-generation devices.
[0003] Polymer materials show great potential for addressing thermal conductivity and heat dissipation issues. However, the intrinsic thermal conductivity of polymer films is low, typically below 0.2 W / (m·K), far lower than that of materials like metals, carbon, and ceramics. This significantly limits their application in high-tech fields. To address this issue, two main approaches have been pursued: modifying the substrate itself and adding highly thermally conductive fillers to the polymer film matrix. However, the addition of highly thermally conductive fillers increases the film thickness, limiting the size of small electronic devices. Therefore, the design of intrinsically thermally conductive polymer films is crucial.
[0004] Constructing an effective thermally conductive filler network and reducing phonon scattering at interfaces are key strategies for obtaining thermally conductive polymer composite films. All-carbon films offer excellent thermal conductivity, light weight, and high flexibility, but they are subject to high production temperatures and costs. Chinese patent CN118650939 A provides a method for preparing ultrahigh thermal conductivity graphene sandwich composite films with a thermal conductivity of 1600–2050 W / mk. However, the carbonization process is performed at 900–1200°C, a high temperature that is unfavorable for cost control. Chinese patent CN218197370 U provides a low-thermal-resistance thermally conductive insulating film consisting of a first thermally conductive phase change layer, a thermally conductive organosilicon layer, a polyimide film, and a second thermally conductive phase change layer. While the film exhibits low thermal resistance and excellent thermal conductivity, it is relatively thick (0.02–0.06 mm), making it unsuitable for application in certain fields. Patent CN115093565 B provides a polyphenylenesulfone ether triazole with excellent high-temperature resistance, demonstrating the heat resistance of the triazole ring. However, the film-forming properties are poor and film-forming is impossible. Therefore, providing a new aromatic imine triazole with excellent high- and low-temperature resistance, thin thickness, good thermal conductivity, and film-forming properties is of great research value. Summary of the Invention
[0005] The present invention aims to provide an aryl imine triazole polymer film and its preparation method and application. The aryl imine triazole polymer film not only has excellent high and low temperature resistance, but also has good film-forming performance and thermal conductivity, and is thin (2-200 mm).
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides an aryl imine triazole polymer film, wherein the aryl imine triazole polymer in the aryl imine triazole polymer film has a structure shown in Formula I:
[0008] Formula I;
[0009] In formula I, R includes or ;
[0010] Ar includes ;
[0011] n=21~100 and n is an integer.
[0012] Preferably, n=21~35 and n is an integer.
[0013] Preferably, the weight average molecular weight Mw of the aromatic imine triazole polymer is 15,000-350,000.
[0014] The present invention provides a method for preparing the aromatic imine triazole polymer film described in the above technical solution, comprising the following steps:
[0015] A diamine monomer having a structure represented by Formula II and a dianhydride monomer having a structure represented by Formula III are mixed with an organic solvent to carry out a polycondensation reaction to obtain a polyamic acid;
[0016] The polyamic acid, the catalyst and the dehydrating agent are mixed to carry out an imidization reaction to obtain an aromatic imine triazole polymer;
[0017] The aryl imine triazole polymer is mixed with an organic solvent, the resulting solution is placed on a substrate, subjected to a gradient temperature increase program, and then peeled and dried to obtain an aryl imine triazole polymer film; Formula II; Formula III;
[0018] In formula II, R includes or , in formula III, Ar includes .
[0019] Preferably, the molar ratio of the diamine monomer to the dianhydride monomer is 1:(1-1.05).
[0020] Preferably, the temperature of the polycondensation reaction is 0-80° C., and the time is 5-7 h.
[0021] Preferably, the dehydrating agent includes anhydrous acetic acid, anhydrous benzoic acid, anhydrous phenolic acid, acetic anhydride, propylene glycol or phosphorus trichloride; the catalyst includes benzyltriethylammonium chloride, tetrabutylammonium bromide, dimethylamine, pyrrole, triethylamine, pyridine or isoquinoline.
[0022] Preferably, the molar ratio of the diamine monomer, the dehydrating agent and the catalyst is (0.2-1):1:(0.2-1); the temperature of the imidization reaction is 25-300° C., and the time is 1-10 h.
[0023] Preferably, the temperature range of the gradient heating is 60-250° C., and the treatment time is 6-16 hours.
[0024] The present invention provides application of the aromatic imine triazole polymer film described in the above technical solution in a thermal conductive film.
[0025] The arylimide-triazole polymer film described herein contains a skeleton structure of benzene and triazole rings, imparting excellent thermal stability and mechanical strength. The strong imide bonds and triazole rings provide high thermal stability and high- and low-temperature resistance. The introduction of triazole rings fosters hydrogen bonding between polymer segments, resulting in a more ordered polymer chain structure. The interlaced and entangled structures between the molecular chains, as well as hydrogen bonding between the side groups, stretch the curled molecular chains, improve the orderliness of the chain aggregation, and create pathways for phonon transmission, thereby enhancing the film-forming properties and intrinsic thermal conductivity of the arylimide-triazole.
[0026] The arylimine triazole polymer film provided by the present invention has a Tg (glass transition temperature) of 254-270°C and a Td10% (10% weight loss temperature in nitrogen) of 621.8-664.2°C. Furthermore, its mechanical properties at -196°C and 25°C exhibit significant temperature invariance, demonstrating that the arylimine triazole polymer film not only has excellent high and low temperature resistance but also possesses excellent mechanical properties. Furthermore, the thermal conductivity of the arylimine triazole at room temperature is 0.45-0.62 W·(m·K). -1 , the thermal conductivity at 200℃ is 0.43~0.6 W·(m·K) -1 , not only has good thermal performance, but also has good thermal conductivity at room temperature and 200°C. The thermal conductivity stability at 200°C can meet the thermal management requirements in many situations. Therefore, the aryl imine triazole polymer film provided by the present invention not only has excellent high and low temperature resistance, but also has good mechanical properties and thermal conductivity.
[0027] The preparation method of the invention efficiently prepares the diamine monomer and the dianhydride monomer through a condensation reaction, has mild reaction conditions and high reaction efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is an infrared comparison image of the diamine monomer Diamine-1 prepared in Example 1 and its raw materials;
[0029] Figure 2 This is an infrared comparison image of PTAI-1 prepared in Example 1 and its raw materials;
[0030] Figure 3 This is an infrared comparison image of the diamine monomer Diamine-2 prepared in Example 2 and its raw materials;
[0031] Figure 4 This is an infrared comparison image of PTAI-2 prepared in Example 2 and its raw materials;
[0032] Figure 5 The DSC graphs of PTAI-1 prepared in Example 1 and PTAI-2 prepared in Example 2 are shown;
[0033] Figure 6 Thermogravimetric diagrams of PTAI-1 prepared in Example 1 and PTAI-2 prepared in Example 2;
[0034] Figure 7 Graphs showing stress-strain data for the PTAI-1 film prepared in Example 1 and the PTAI-2 film prepared in Example 1;
[0035] Figure 8 Graph showing the thermal conductivity data of the PTAI-1 film prepared in Example 1 and the PTAI-2 film prepared in Example 1. DETAILED DESCRIPTION
[0036] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0037] The present invention provides an aryl imine triazole polymer film, wherein the aryl imine triazole polymer in the aryl imine triazole polymer film has a structure shown in Formula I:
[0038] Formula I;
[0039] In formula I, R includes or ;
[0040] Ar includes ;
[0041] n=21~100 and n is an integer.
[0042] In the present invention, n=21-35 and n is an integer, more preferably 26-28.
[0043] In the present invention, the weight average molecular weight Mw of the aromatic imine triazole polymer is 15,000-350,000.
[0044] In the present invention, the aromatic imine triazole polymer is preferably
[0045]
[0046] or
[0047] The present invention provides a method for preparing the aromatic imine triazole polymer film described in the above technical solution, comprising the following steps:
[0048] A diamine monomer having a structure represented by Formula II and a dianhydride monomer having a structure represented by Formula III are mixed with an organic solvent to carry out a polycondensation reaction to obtain a polyamic acid;
[0049] The polyamic acid, the catalyst and the dehydrating agent are mixed to carry out an imidization reaction to obtain an aromatic imine triazole polymer;
[0050] The aryl imine triazole polymer is mixed with an organic solvent, the resulting solution is placed on a substrate, subjected to a gradient temperature increase program, and then peeled and dried to obtain an aryl imine triazole polymer film; Formula II; Formula III;
[0051] In formula II, R includes or , in formula III, Ar includes .
[0052] In the present invention, the diamine monomer having the structure of Formula II is preferably prepared by mixing a 4,4'-diazide compound, m-aminophenylacetylene, a catalyst, and an organic solvent under nitrogen conditions to perform a click polymerization reaction to obtain the diamine monomer. The 4,4'-diazide compound is preferably 4,4'-diazide diphenyl sulfone or 4,4'-diazide diphenyl ether. The 4,4'-diazide diphenyl sulfone or 4,4'-diazide diphenyl ether is prepared according to the method disclosed in Patent CN 118684885 A.
[0053] In the present invention, the molar ratio of the 4,4'-diazide compound to m-aminophenylacetylene is preferably 1:(1.5-3), more preferably 1:2.
[0054] In the present invention, the catalyst is preferably copper sulfate pentahydrate and sodium ascorbate; and the molar ratio of the 4,4'-diazide compound to copper sulfate pentahydrate and sodium ascorbate is preferably 0.01:0.005:0.01.
[0055] In the present invention, the organic solvent used in the click polymerization reaction is preferably N,N-dimethylacetamide; the present invention has no special limitation on the amount of the organic solvent used, and the amount can be adjusted according to actual needs to ensure that the reaction proceeds smoothly.
[0056] In the present invention, the temperature of the click polymerization reaction is preferably 50-70° C., more preferably 60° C., and the time is preferably 5-7 h, more preferably 6 h.
[0057] After the click polymerization reaction is completed, the present invention preferably adds the obtained product dropwise into a stirred saturated disodium ethylenediaminetetraacetic acid aqueous solution to obtain a light yellow precipitate, which is filtered out and freeze-dried to obtain a diamine monomer.
[0058] In the present invention, the dianhydride monomer having the structure represented by Formula III is preferably 4,4'-oxydiphthalic anhydride.
[0059] In the present invention, the molar ratio of the diamine monomer to the dianhydride monomer is preferably 1:(1-1.05), more preferably 1:(1-1.02).
[0060] The organic solvent used in the polycondensation reaction is preferably N,N-dimethylacetamide ; The present invention has no particular limitation on the amount of the organic solvent used, and the amount can be adjusted according to actual needs to ensure that the reaction proceeds smoothly.
[0061] In the present invention, the diamine monomer is preferably dissolved in an organic solvent, and then the dianhydride monomer is added in three equal portions to carry out a polycondensation reaction.
[0062] In the present invention, the temperature of the polycondensation reaction is preferably 0-80° C., more preferably 5-50° C., and the time is preferably 5-7 h, more preferably 6 h; and the polycondensation reaction is preferably carried out in an ice bath.
[0063] After the polycondensation reaction, the present invention preferably does not perform any treatment, and directly adds a dehydrating agent and a catalyst to the obtained product solution to carry out an imidization reaction (chemical imidization dehydration).
[0064] In the present invention, the dehydrating agent preferably includes anhydrous acetic acid, anhydrous benzoic acid, anhydrous phenolic acid, acetic anhydride, propylene glycol or phosphorus trichloride; the catalyst preferably includes benzyltriethylammonium chloride, tetrabutylammonium bromide, dimethylamine, pyrrole, triethylamine, pyridine or isoquinoline; the molar ratio of the diamine monomer, the dehydrating agent and the catalyst is preferably (0.2~1):1:(0.2~1), more preferably 0.5:1:0.5.
[0065] In the present invention, the temperature of the imidization reaction is preferably 25-300° C., more preferably 200° C., and the time is preferably 1-10 h, more preferably 4 h.
[0066] After the imidization reaction is completed, the present invention preferably adds the obtained product dropwise into rapidly stirred deionized water, collects the precipitate by suction filtration, and freeze-dries for 24 hours to obtain an aromatic imine triazole polymer.
[0067] After obtaining the aryl imine triazole polymer, the present invention mixes the aryl imine triazole polymer with an organic solvent, places the obtained solution on a substrate, performs a gradient temperature increase program, and then peels and dries to obtain an aryl imine triazole polymer film.
[0068] The present invention preferably dissolves an aryl imine triazole polymer in an organic solvent (preferably N,N-dimethylacetamide) to obtain a polymer solution with a concentration of 10 to 15 wt% (more preferably 13 wt%). The polymer solution is spread on a clean glass sheet by a casting method or a film drawing method. After a gradient temperature increase procedure, the solution is cooled to room temperature. The glass sheet is immersed in deionized water, peeled and dried to obtain an aryl imine triazole polymer film.
[0069] In the present invention, the thickness of the aryl imine triazole polymer film is preferably 2 to 200 mm, more preferably 5.2 to 5.8 mm.
[0070] In the present invention, the temperature range of the gradient heating is preferably 60-250°C, and the treatment time is preferably 6-16 hours; the gradient heating program is more preferably 60°C / 12 hours, 80°C / 2 hours, 100°C / 1 hour, and 200°C / 1 hour.
[0071] The present invention provides the application of the aromatic imine triazole polymer described in the above technical solution in a thermal conductive film. The present invention has no particular limitation on the application method, and the application can be carried out according to methods well known in the art.
[0072] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0073] Example 1
[0074] This example provides the preparation of an aryl imine triazole polymer film:
[0075] (1) Add 0.01 mol of 4,4'-diazide diphenyl sulfone (prepared according to patent CN 118684885 A) and 100 mL of N,N-dimethylacetamide to a 250 mL three-necked flask under nitrogen gas protection and magnetic stirring heating. After dissolution, add 0.02 mol of m-aminophenylacetylene, and then add 0.005 mol of copper sulfate pentahydrate and 0.01 mol of sodium ascorbate in sequence. Heat and stir at 60°C for 6 h. After the reaction is completed, the obtained product solution is added dropwise to a stirred saturated disodium ethylenediaminetetraacetic acid aqueous solution to obtain a light yellow precipitate. After filtration, the precipitate is freeze-dried to obtain the diamine monomer Diamine-1.
[0076] (2) Add 0.01 mol of diamine monomer Diamine-1 and 100 mL of N,N-dimethylacetamide to a 250 mL three-necked flask under nitrogen gas protection and magnetic stirring heating device. After stirring at room temperature, add 0.0102 mol of 4,4'-oxydiphthalic anhydride in three times under ice bath, continue to react at 5°C for 6 hours, add 0.02 mol of dehydrating agent acetic anhydride and 0.01 mol of catalyst triethylamine, stir at 25°C for 4 hours, pour the resulting solution into deionized water for precipitation, filter and wash with deionized water three times until the pH value of the filtrate is 7, and dry the resulting precipitate in a freeze dryer for 24 hours to obtain an aromatic imine triazole polymer PTAI-1, the structural formula of which is shown below;
[0077] (3) PTAI-1 was dissolved in N,N-dimethylacetamide to obtain a viscous solution with a concentration of 13 wt%, which was poured onto a clean glass plate by a casting method. After a gradient heating program of 60℃ / 12 h, 80℃ / 2 h, 100℃ / 1 h, and 200℃ / 1 h, the glass plate was immersed in deionized water after reaching room temperature. After peeling and drying, a PTAI-1 film with a thickness of 5.2 mm was obtained.
[0078]
[0079] Example 2
[0080] This example provides the preparation of an aryl imine triazole polymer film:
[0081] (1) Add 0.01 mol of 4,4'-diazide diphenyl ether (prepared according to patent CN 118684885 A) and 100 mL of N,N-dimethylacetamide to a 250 mL three-necked flask under nitrogen gas protection and magnetic stirring heating. After dissolution, add 0.02 mol of m-aminophenylacetylene, and then add 0.005 mol of copper sulfate pentahydrate and 0.01 mol of sodium ascorbate in sequence. Heat and stir at 60°C for 6 h. After the reaction is completed, the obtained product solution is added dropwise to a stirred saturated disodium ethylenediaminetetraacetic acid aqueous solution to obtain a light yellow precipitate. After filtration, the precipitate is freeze-dried to obtain the diamine monomer Diamine-2.
[0082] (2) Add 0.01 mol of diamine monomer Diamine-2 and 100 mL of N,N-dimethylacetamide to a 250 mL three-necked flask under nitrogen gas protection and magnetic stirring heating device. After stirring at room temperature, add 0.0102 mol of 4,4'-oxydiphthalic anhydride in three times under ice bath, continue to react at 5°C for 6 hours, add 0.02 mol of dehydrating agent acetic anhydride and 0.01 mol of catalyst triethylamine, stir at 25°C for 4 hours, pour the resulting solution into deionized water for precipitation, filter and wash with deionized water three times until the pH value of the filtrate is 7, and dry the resulting precipitate in a freeze dryer for 24 hours to obtain an aromatic imine triazole polymer PTAI-2, the structural formula of which is shown below;
[0083] (3) PTAI-2 was dissolved in N,N-dimethylacetamide to obtain a viscous solution with a concentration of 13 wt%, which was poured onto a clean glass plate by a casting method. After a gradient heating program of 60℃ / 12 h, 80℃ / 2 h, 100℃ / 1 h, and 200℃ / 1 h, the glass plate was immersed in deionized water after reaching room temperature. After peeling and drying, a PTAI-2 film with a thickness of 5.8 mm was obtained.
[0084]
[0085] Characterization
[0086] Figure 1 This is an infrared comparison of the diamine monomer Diamine-1 and its raw materials prepared in Example 1; wherein a is 4,4'-diazide diphenyl sulfone, b is m-aminophenyl acetylene, and c is Diamine-1. Figure 1 It can be seen that the 3286 cm -1 and 2113cm -1 The absorption peaks of C≡CH and -N3 disappear at 3129 cm -1 The characteristic vibration absorption peak of -CH on the triazole ring appears at 3400 cm-1 The double peak of amino group appeared nearby, which verified the successful preparation of diamine monomer Diamine-1.
[0087] Figure 2 This is an infrared comparison of PTAI-1 prepared in Example 1 and its raw materials; wherein a is Diamine-1, b is 4,4-oxydiphthalic anhydride, and c is PTAI-1. Figure 2 It can be seen that at wave number 1774 cm -1 and 1713 cm -1 The asymmetric and symmetric stretching peaks of the carbonyl group (-C=O) on the imide ring appeared at 1367 cm -1 The peak at 746 cm is attributed to the -CN stretching peak on the imide ring. -1 The absorption peak at 1593 cm-1 is attributed to the bending vibration of -C=O on the imide ring. -1 The characteristic peak of polyamide acid is 1710 cm -1 (stretching vibration peak of carboxyl-CO), 1660 cm -1 (amide CO), 1550 cm -1 (Amide CN) was absent, indicating that the imidization was almost complete, preliminarily judging that PTAI-1 was successfully prepared.
[0088] Figure 3 This is an infrared comparison of the diamine monomer Diamine-2 prepared in Example 2 and its raw materials; wherein a is 4,4'-diazide diphenyl ether, b is m-aminophenylacetylene, and c is Diamine-2. Figure 3 It can be seen that the 3286 cm -1 and 2122cm -1 The absorption peaks of C≡CH and -N3 disappear at 3123 cm -1 The characteristic vibration absorption peak of -CH on the triazole ring appears at 3400 cm -1 The double peak of amino group appeared nearby, which verified the successful preparation of diamine monomer Diamine-1.
[0089] Figure 4 This is an infrared comparison of PTAI-2 prepared in Example 2 and its raw materials; wherein a is Diamine-2, b is 4,4-oxydiphthalic anhydride, and c is PTAI-2. Figure 4 It can be seen that at wave number 1774 cm -1 and 1713 cm -1 The asymmetric and symmetric stretching peaks of the carbonyl group (-C=O) on the imide ring appeared at 1367 cm -1The peak at 746 cm is attributed to the -CN stretching peak on the imide ring. -1 The absorption peak at 1593 cm-1 is attributed to the bending vibration of -C=O on the imide ring. -1 The characteristic peak of polyamide acid is 1710 cm -1 (stretching vibration peak of carboxyl-CO), 1660 cm -1 (amide CO), 1550 cm -1 (Amide CN) was absent, indicating that the imidization was almost complete, and preliminarily judging that PTAI-2 was successfully prepared.
[0090] Performance Testing
[0091] (1) Determination of molecular weight and distribution coefficient
[0092] The molecular weight and distribution coefficient of PTAI-1 and PTAI-2 provided in Examples 1 and 2 were measured, and the results are shown in Table 1.
[0093] Table 1 Molecular weight and distribution coefficient of PTAI-1 and PTAI-2 provided in Examples 1 and 2
[0094]
[0095] As shown in Table 1, both PTAI-1 and PTAI-2 have relatively high molecular weight and narrow molecular weight distribution, and have the conditions for film formation.
[0096] (2) Viscosity test
[0097] The viscosity of PTAI-1 and PTAI-2, provided in Examples 1 and 2, was measured using an Ubbelohde viscometer to measure the intrinsic viscosity of the polymer solutions. N,N-dimethylacetamide (DMAc) was used as the solvent, the initial concentration of the polymer solution was 15 wt%, and the test temperature was set at 25°C. The results are shown in Table 2.
[0098] Table 2 Intrinsic viscosity of PTAI-1 and PTAI-2 provided in Examples 1 and 2
[0099]
[0100] As can be seen from Table 2, in the systems of PTAI-1 and PTAI-2, the intermediate polyamic acid PAA has a relatively high intrinsic viscosity value, which provides the possibility for subsequent film formation.
[0101] (3) Thermal performance test
[0102] The thermal properties of PTAI-1 and PTAI-2 provided in Examples 1 and 2 were tested. The DSC test process and conditions were as follows: heating from 40°C to 300°C at a heating rate of 10°C / min, cooling to 40°C at a cooling rate of 30°C / min, and finally heating to 250°C at a heating rate of 10°C / min.
[0103] The thermogravimetric test was carried out in a nitrogen atmosphere with a protective gas flow rate of 30 mL / min and a purge gas flow rate of 30 ml / min. The temperature was raised from 40°C to 600°C at a heating rate of 10°C / min to obtain a thermogravimetric spectrum of the sample.
[0104] Figure 5 The DSC graphs of PTAI-1 prepared in Example 1 and PTAI-2 prepared in Example 2 are shown; Figure 6 The thermogravimetric diagrams of PTAI-1 prepared in Example 1 and PTAI-2 prepared in Example 2.
[0105] Table 3 Thermal performance test results of PTAI-1 and PTAI-2
[0106]
[0107] from Figure 5 、 Figure 6 As shown in Table 3, PTAI-1 and PTAI-2 have better high temperature resistance.
[0108] (4) High and low temperature performance test
[0109] The high and low temperature performance of the PTAI-1 membrane and the PTAI-2 membrane prepared in Examples 1 and 2 were tested using a universal testing machine.
[0110] The film was cut into dumbbell-shaped specimens according to GBT 1040-92. The tensile rate was set to 10 mm / min. The tensile tests were carried out at -196℃ and 25℃ respectively. The test results are shown in Figure 7 .
[0111] Figure 7 The stress-strain data diagram of the PTAI-1 film prepared in Example 1 and the PTAI-2 film prepared in Example 2 is shown in FIG. Figure 7 As shown, the film exhibits significant temperature-invariant mechanical properties at -196°C and 25°C, which is very important for applications in extreme environments. This proves that the film's mechanical properties are not greatly affected by extreme temperatures and can be used in extremely cold conditions.
[0112] (5) Thermal conductivity test
[0113] The thermal conductivity of the PTAI-1 film and the PTAI-2 film provided in Examples 1 and 2 was tested by annealing at room temperature 25°C and 200°C for 1 hour. Figure 8 As shown, after annealing, the change in thermal conductivity is within the experimental error range, and the thermal conductivity stability at 200 °C can meet the thermal management requirements in many cases.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. An aromatic imine triazole polymer film, characterized in that: The aryl imine triazole polymer in the aryl imine triazole polymer film has a structure shown in Formula I: Formula I; In Formula I, R includes or ; Ar includes ; n=21~100 and n is an integer.
2. The aryl imine triazole polymer film according to claim 1, characterized in that: n=21~35 and n is an integer.
3. The aryl imine triazole polymer film according to claim 1, characterized in that: The weight average molecular weight Mw of the aromatic imine triazole polymer is 15000-350000.
4. The method for preparing the aryl imine triazole polymer film according to any one of claims 1 to 3, characterized in that: The following steps are involved: A diamine monomer having a structure shown in Formula II and a dianhydride monomer having a structure shown in Formula III are mixed with an organic solvent to carry out a polycondensation reaction to obtain a polyamic acid; The polyamic acid, the catalyst and the dehydrating agent are mixed to carry out imidization reaction to obtain an aromatic imide triazole polymer; The aryl imine triazole polymer is mixed with an organic solvent, the obtained solution is placed on a substrate, a gradient temperature program is performed, and then the solution is peeled off and dried to obtain an aryl imine triazole polymer film; Formula II; Formula III; In formula II, R includes or , in formula III, Ar includes .
5. The preparation method according to claim 4, characterized in that: The molar ratio of the diamine monomer to the dianhydride monomer is 1:(1-1.05).
6. The preparation method according to claim 5, characterized in that: The temperature of the polycondensation reaction is 0-80°C and the time is 5-7 h.
7. The preparation method according to claim 4, characterized in that: The dehydrating agent includes anhydrous acetic acid, anhydrous benzoic acid, anhydrous phenolic acid, acetic anhydride, propylene glycol or phosphorus trichloride; the catalyst includes benzyltriethylammonium chloride, tetrabutylammonium bromide, dimethylamine, pyrrole, triethylamine, pyridine or isoquinoline.
8. The preparation method according to claim 7, characterized in that: The molar ratio of the diamine monomer, the dehydrating agent and the catalyst is (0.2-1):1:(0.2-1); the temperature of the imidization reaction is 25-300° C., and the time is 1-10 h.
9. The preparation method according to claim 4, characterized in that: The temperature range of the gradient heating is 60-250° C., and the treatment time is 6-16 hours.
10. Use of the aryl imine triazole polymer film according to any one of claims 1 to 3 or the aryl imine triazole polymer film prepared by the preparation method according to any one of claims 4 to 9 in a thermal conductive film.
Citation Information
Patent Citations
A kind of polyphenylsulfone ether triazole and its preparation method and application
CN115093565B
Ultrahigh-heat-conductivity graphene composite film as well as preparation method and application thereof
CN118650939A
Low-thermal-resistance heat-conducting insulating film
CN218197370U
Polyamine containing triazole ring and preparation method and application thereof
CN101774973A
Aryl ether imide polytriazole as well as preparation method and application thereof
CN118684885A